Outcome with Methotrexate versus Expectant Management for Ectopic Pregnancy - Ayesha Abdul Sattar, Sumaira Nadeem, Madiha Fatima, Samia Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients with ectopic pregnancy and low serum β-HCG concentrations are commonly treated with systemic methotrexate. Aim: To compare the outcome of methotrexate versus expectant management for females presenting with ectopic pregnancy. Study design: Randomized controlled trial. Methodology: Females with ectopic pregnancy (n=140) were enrolled in study. Blood sample was taken and beta-HCG was noted. Then females were randomly divided in two groups by using lottery method. In group A, females were given methotrexate. In group B, females were given expectant management and not received any specific treatment. Then females were followed-up for 24 hours for assessment of decline in HCG was labeled. If HCG was not declined or even increase, then females underwent surgical intervention. Data was evaluated by using SPSS v.24. Results: The mean age of patients randomized to methotrexate group was 31.24±8.85years while in expectant management group was 29.94±8.02 years. In methotrexate group, 67(95.7%) females had decline in beta-HCG while 3(4.3%) had no decline in beta-HCG. In expectant management group, 37(52.9%) females had decline in beta-HCG while 33(47.1%) had no decline in beta-HCG. Practical Implication: As there is a high incidence of ectopic pregnancies among our pregnant females and there is lack of local data that specifically addresses this health issue thus current study was planned. Conclusion: It was concluded that methotrexate is an effective way to treat ectopic pregnancy with less chances of complications. Keywords: Ectopic Pregnancy, Methotrexate, Beta-Human Chorionic Gonadotropin and Surgical Intervention.